Large-strain consolidation model considering radial transfer attenuation of vacuum pressure. (June 2020) - Wang, Jianhua; Ding, Jianwen; Wang, Heng; Mou, Cong
Abstract: This paper proposes a large-strain consolidation model that can consider radial transfer attenuation of vacuum pressure. In order to facilitate the solution, this proposed model is rewritten to take hydraulic head as the independent variable that can reduce the computational complexity. The universality of the proposed model is discussed based on the comparisons with several existing typical models. It is found that the proposed large-strain consolidation model has better applicability and can incorporate the attenuation of vacuum pressure. That's to say, the model is more universal and can be simplified to typical models under restrictive conditions. In addition, the comparisons between numerical results and laboratory measurements indicate that the proposed model considering radial attenuation of vacuum pressure can better describe the dissipation law of excess pore-water pressure. Meanwhile, the proposed model can be utilized for the different combinations of surcharge pressure and vacuum pressure.